Individualized Coaching to Improve Teacher Practice Across Grades and Subjects: New Experimental Evidence - Kraft, Matthew A.; Blazar, David (Educational policy (Los Altos, Calif.), 2017)
This article analyzes a coaching model focused on classroom management skills and instructional practices across grade levels and subject areas. We describe the design and implementation of MATCH Teacher Coaching among an initial cohort of 59 teachers working in New Orleans charter schools. We evaluate the effect of the program on teachers’ instructional practices using a block randomized trial and find that coached teachers scored 0.59 standard deviations higher on an index of effective teaching practices comprised of observation scores, principal evaluations, and student surveys. We discuss implementation challenges and make recommendations for researcher–practitioner partnerships to address key remaining questions.